Investigation of High-Temperature Wear Behaviour of AA 2618-Nano Si3N4 Composites Using Statistical Techniques. (16th September 2022) - George, Santhi M.; Gacem, Amel; Kistan, A.; Ashick, R. Mohammed; Rao, L. Malleswara; Rajput, Vinod Singh; Nagabooshanam, N.; Refat, Moamen S.; Alsuhaibani, Amnah Mohammed; Christopher, David
Abstract : The wear behaviour of hot pressed AA 2618 aluminium alloy matrix composites reinforced through nano Si3 N4 elements (1 percent and 2 percent) has been investigated in this paper. Temperatures of 50°C, 150°C, and 250°C were used to examine the tribological characteristics of the models under a range of loads and pressures. The best wear performance was found in AA 2618/2wt percent Si3 N4 . Under a load of 30 N and temperature of 250°C, it was discovered that Si3N4-enriched AA 2618 alloy was 35.7% more wear-resistant than unreinforced AA 2618 alloy. Metal flow and plain delamination were the most common wear mechanisms at higher temperatures. Delamination is the most common wear mechanism at temperatures between 50 and 250 degrees Celsius. In the analysis of variance, the wear rate was influenced by temperature, load, and the presence of Si3 N4 by 47.2%. In order to predict the wear rate, regression equations (linear and nonlinear) were developed by Taguchi method. Using a high determination coefficient, the nonlinear regression was the preeminent success rate (92.8 percent).